High-efficiency SOI-based metalenses at telecommunication wavelengths - Ryu Taesu; Kim Moohyuk; Hwang Yongsop; Kim Myung-Ki; Yang Jin-Kyu (Nanophotonics, 2022)
We demonstrated silicon-on-insulator (SOI)-based high-efficiency metalenses at telecommunication wavelengths that are integrable with a standard 220 nm-thick silicon photonic chip. A negative electron-beam resist (ma-N) was placed on top of the Si nanodisk, providing vertical symmetry to realize high efficiency. A metasurface with a Si/ma-N disk array was numerically investigated to design a metalens that showed that a Si/ma-N metalens could focus the incident beam six times stronger than a Si metalens without ma-N. Metalenses with a thick ma-N layer have been experimentally demonstrated to focus the beam strongly at the focal point and have a long depth of field at telecommunication wavelengths. A short focal length of 10 μm with a wavelength-scale spot diameter of approximately 2.5 μm was realized at 1530 nm. This miniaturized high-efficiency metalens with a short focal length can provide a platform for ultrasensitive sensors on silicon photonic IC.